Faktor-Faktor yang Mempengaruhi Produksi Usahatani Jeruk Manis Siam Madu (Citrus sinensis nobilis) di Desa Tanea Kecamatan Konda Kabupaten Konawe Selatan - Aan Setiadi; Abdul Gafaruddin; Agustono Slamet (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This study aims to determine the factors that influence the production of citrus farming in Tanea Village, Konda District, South Konawe Regency. The population in this study amounted to 30 heads of families (KK). This study determined the sample by census, i.e., the entire population was sampled. The variable used in this research is the characteristics of farmers, including the number of family members (persons), age (years), education level, number of family dependents, and citrus farming experience. Other variables affect production, including labor, plant age, number of trees, fertilizers, and pesticides. Analysis of the data used is multiple linear regression analysis. The results showed that the factors that influenced the production of sweet orange farming in Tanea Village were the number of trees and the age of the plant. Both factors had a positive and significant effect on increasing the production of sweet oranges. Increasing the number of trees by 1% will increase the production of sweet oranges by 1,072 kg/ha. Adding 1% plant age will be followed by an increase in lovely orange output of 1,140 kg/ha. Adding and reducing the number of workers by 1% does not affect the production produced by sweet orange farmers. Adding or decreasing 1% of fertilizer cannot affect the sweet oranges produced. Adding and reducing the amount of 1% pesticide does not affect the resulting production. The average output of sweet oranges in Tanea Village is 1,945 kg/harvest season, with the highest show being 12000 kg and the lowest being 100 kg.